Molecular Targets and Nanoparticulate Systems Designed for the Improved Therapeutic Intervention in Glioblastoma Multiforme - Akhter, Md. Habban; Rizwanullah, Md.; Ahmad, Javed; Amin, Saima; Ahmad, Mohammad Zaki; Minhaj, Md. Akram; Mujtaba, Md. Ali; Ali, Javed (Drug Research, 2020)
Glioblastoma multiforme (GBM) is the most aggressive and fatal CNS related tumors, which is responsible for about 4% of cancer-related deaths. Current GBM therapy includes surgery, radiation, and chemotherapy. The effective chemotherapy of GBM is compromised by two barriers, i. e., the blood-brain barrier (BBB) and the blood tumor barrier (BTB). Therefore, novel therapeutic approaches are needed. Nanoparticles are one of the highly efficient drug delivery systems for a variety of chemotherapeutics that have gained massive attention from the last three decades. Perfectly designed nanoparticles have the ability to cross BBB and BTB and precisely deliver the chemotherapeutics to GBM tissue/cells. Nanoparticles can encapsulate both hydrophilic and lipophilic drugs, genes, proteins, and peptides, increase the stability of drugs by protecting them from degradation, improve plasma half-life, reduce adverse effects and control the release of drugs/genes at the desired site. This review focussed on the different signaling pathways altered in GBM cells to understand the rationale behind selecting new therapeutic targets, challenges in the drug delivery to the GBM, various transport routes in brain delivery, and recent advances in targeted delivery of different drug and gene loaded various lipidic, polymeric and inorganic nanoparticles in the effective management of GBM.
Keywords: drug delivery; pharmaceutics; cancer; anticancer drugs